Epidural Anesthesia Management for Unilateral Salpingo-Oophorectomy in Patients with Ovarian Mass : A Case Report - Ksatriaputra, Alesandro; Saputra, Taufik; Paramita, Dina (Jurnal Komplikasi Anestesi, 2023)
with sedation and mainly used in elderly patients or those with medical problems, including those who had ovarian mass. Epidural administration of amide local anesthetics in combination with opioids is widely used for pain relief because of the dose minimizing and side effects reducing benefits. Case: Patient was diagnosed with ovarian mass. The patient also had pleural effusion, ascites, and hypoalbuminemia. Epidural anesthesia used in this patient as a resource for perioperative and postoperative pain management. Discussion: Patient underwent unilateral salpingo-oophorectomy for her ovarian mass. Anesthetic doses were given carefully due to patient conditions with pleural effusion and ascites. Opioid and Neuromuscular Blocking Agents (NMBAs) effects were absolutely decreased due to hypoalbuminemia, but were overcome with Naloxone and Sugammadex. Epidural anesthesia used to stabilize the drugs and pain management for this patient. Conclusion: Epidural anesthesia is an excellent choice for unilateral salpingo-oophorectomy in patients with ovarian mass. It has been proven to provide excellent pain control after major surgeries and may be associated with a lower incidence of postoperative complications.